2014
DOI: 10.1111/pace.12517
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Anticoagulation Management in Patients on Chronic Oral Anticoagulant Therapy Undergoing Cardiac Devices Implantation: A Meta‐Analysis

Abstract: The perioperative anticoagulation strategy during cardiac implantable electronic devices (CIEDs) implantation is highly variable without consensus among implanting physicians. A systematic literature search was performed in MEDLINE, EMBASE, and the Cochrane Library to identify clinical trials in patients on chronic oral anticoagulant (OAC) therapy undergoing CIEDs implantation. Bleeding and thromboembolic events were compared among heparin bridging, continued OAC, and interrupted OAC groups. Data were expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…This study showed no difference in the incidence of TE events or major bleeding complications between the two groups [23]. Two subsequent metaanalyses have shown findings consistent with those of the BRUISE CONTROL and COMPARE trials, including one that included 3744 patients from 14 studies, and found that, in patients undergoing cardiac device implantation, heparin bridging conferred a significantly higher risk of bleeding than continuation of OAC therapy (hazard ratio 3.1; 95% confidence interval [CI] 2.0-4.8), with no significant reduction in the frequency of TE events [20,22]. Together, and as summarized in Table 3, these findings indicate that there are an increasing number of minor procedure/surgery types that can be safely performed without interruption of VKA therapy.…”
Section: Overall Periprocedural Antithrombotic Strategymentioning
confidence: 90%
See 1 more Smart Citation
“…This study showed no difference in the incidence of TE events or major bleeding complications between the two groups [23]. Two subsequent metaanalyses have shown findings consistent with those of the BRUISE CONTROL and COMPARE trials, including one that included 3744 patients from 14 studies, and found that, in patients undergoing cardiac device implantation, heparin bridging conferred a significantly higher risk of bleeding than continuation of OAC therapy (hazard ratio 3.1; 95% confidence interval [CI] 2.0-4.8), with no significant reduction in the frequency of TE events [20,22]. Together, and as summarized in Table 3, these findings indicate that there are an increasing number of minor procedure/surgery types that can be safely performed without interruption of VKA therapy.…”
Section: Overall Periprocedural Antithrombotic Strategymentioning
confidence: 90%
“…There are low-quality to moderate-quality data showing that therapy with VKAs, including warfarin, acenocoumarol, and phenprocoumon, does not require interruption for minor procedures, as shown in Table 2. These include dental procedures (tooth extraction; root canal), skin procedures (biopsy; skin cancer removal), and cataract surgery [20][21][22][23][24][25][26][27]. The 2012 ACCP Antithrombotic Therapy Guidelines give only weak Grade 2C recommendations for continuing VKA therapy in these specific situations involving minor procedures, as they have been associated with a low risk of bleeding [3].…”
Section: Overall Periprocedural Antithrombotic Strategymentioning
confidence: 99%
“…1,2 However, a casecontrol study, meta-analysis and randomized controlled studies have indicated a significantly increased risk of bleeding in patients undergoing heparin replacement instead of continued warfarin therapy. 21,[25][26][27][28][29][30] When a comparison was made between heparin replacement and continued warfarin treatment in terms of pacemaker implantation and atrial fibrillation ablation, no difference was found in thrombosis development, and continued warfarin treatment resulted in a significantly lower incidence of bleeding. 31,32 The risk of postoperative bleeding following endoscopic procedures during warfarin treatment may be reduced by maintaining the PT-INR at the low end of the therapeutic range on the day prior to or on the day of the procedure.…”
Section: Further Informationmentioning
confidence: 99%
“…The previous guidelines (2012) recommended replacing warfarin with heparin in gastroenterological endoscopic procedures with a high risk of bleeding . However, a case–control study, meta‐analysis and randomized controlled studies have indicated a significantly increased risk of bleeding in patients undergoing heparin replacement instead of continued warfarin therapy . When a comparison was made between heparin replacement and continued warfarin treatment in terms of pacemaker implantation and atrial fibrillation ablation, no difference was found in thrombosis development, and continued warfarin treatment resulted in a significantly lower incidence of bleeding .…”
Section: Statements 1–7mentioning
confidence: 99%
“…Compared with uninterrupted vitamin K antagonist therapy, bridging with heparin or LMWH resulted in a higher risk of bleeding events (RR, 3.10; 95% CI, 2.02–4.76; P < .00001) and pocket hematoma (RR, 3.58; 95% CI, 2.17–5.91; P < .00001), with no difference in thromboembolic risk (RR, 1.16; 95% CI, 0.36–3.67; P = .81). 18…”
Section: Discussionmentioning
confidence: 99%